Eurosystem collateral policy and framework: Post-Lehman time as a new collateral space - Ansgar Belke (Intereconomics, 2015)
Collateral plays a central role in monetary policy. In recent years, its importance has increased as uncollateralised inter-bank borrowing has gradually been replaced by collateralised central bank lending. This has in turn affected collateral availability and the need for high-quality assets. The European Central Bank has reacted to this development by creating a series of different measures to broaden collateral availability, including changing the eligibility rules (e.g. reducing rating thresholds for certain asset classes) or extending the eligible assets (e.g. allowing national central banks to accept bank loans as collateral). In the context of these developments, this article assesses and comments on various aspects of the Eurosystem collateral policy and overall framework. In particular, it examines the economic implications of the current ECB collateral policy for asset allocation and relative asset price developments from a cross-country perspective.
Keywords: 330; Geldpolitik; Finanzkrise; Kreditsicherung; Bankrisiko; Eurozone